2001
DOI: 10.1086/324428
|View full text |Cite
|
Sign up to set email alerts
|

Host Cell–Specific Expression of a p44 Epitope by the Human Granulocytic Ehrlichiosis Agent

Abstract: The human granulocytic ehrlichiosis agent (HGEa) survives extreme differences between ticks and humans, possibly by use of differential expression of specific antigens for survival in different hosts. The role of the immunodominant p44 antigens is unknown. In this study, HGEa cultured in human or tick cells was probed with human, mouse, and hamster serum and with monoclonal antibodies (MAbs). p44 antigens were strongly expressed in human HL-60 cells but were strikingly reduced in tick cells. In HGEa alternatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 31 publications
4
26
1
Order By: Relevance
“…When the pathogen was transferred to the I. scapularis cell line ISE6 growing at 34°C, downregulation of a specific P44 antigen was observed in Western blots using a monoclonal antibody. This effect was not temperature dependent, since it was also seen in tick cells maintained at 37°C, but upregulation occurred after the pathogen was returned to HL-60 cells (16).…”
Section: Discussionmentioning
confidence: 82%
“…When the pathogen was transferred to the I. scapularis cell line ISE6 growing at 34°C, downregulation of a specific P44 antigen was observed in Western blots using a monoclonal antibody. This effect was not temperature dependent, since it was also seen in tick cells maintained at 37°C, but upregulation occurred after the pathogen was returned to HL-60 cells (16).…”
Section: Discussionmentioning
confidence: 82%
“…For example, levels of expression of the major surface proteins MSP1a and 1b in tick cells and bovine erythrocytes correlated with their roles as adhesins for the different host cells [44], and levels of expression of outer membrane proteins encoded by the msp2 gene superfamily differed markedly between tick and bovine cells [45]. In A. phagocytophilum, the immunodominant p44 antigen predominated in human cells but not in tick cells and might be involved in regulatory changes that mediate survival of the pathogen by immune modulation after tick transmission [46]. The p44 gene expression site was found to be polymorphic in human and tick cells, with sequence changes in p44 variants being influenced by host cell type and culture conditions [47].…”
Section: Pathogen Genomics and Proteomicsmentioning
confidence: 98%
“…Each expressed p44 can be identified by its signature central hypervariable sequence. While many studies have shown expression of different p44 species in different host environments (3,15,16,18,30,34), little is known about the regulation of p44 transcription. Unlike the well-studied bovine erythrocytic agent Anaplasma marginale, which has a single full-length msp2 gene and thus a single msp2 expression locus (4), there are many full-length p44 genes in the A. phagocytophilum genome which need to be examined.…”
mentioning
confidence: 99%